Painting of dilapidated Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Painting of dilapidated Sitaleshwar Temple in the Chandrabhaga temple complex (After Fergusson 1848). Image courtesy: Wikimedia Commons